PENENTUAN BIAYA PEMERIKSAAN DENGAN METODE ACTIVITY BASED COSTING PADA LABORATORIUM KLINIK PRIMA - Utami, Indah Setya; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
At this time the competition in the business world is not come from local competitors but it also comes from international competitors. In order to win the competition, companies must have high competitiveness in characterizing qualified product and cost effectiveness. This research is meant to find out the implementation of activity based costing in determining the laboratory diagnostic service cost at Laboratorium Klinik Prima accurately. The activity based costing method is conducted by identifying activities and correlating it with cost driver to calculate cost pool rate in the allocation of overhead cost, so cost distortion does not occur in the determination of diagnostic cost. The result of this research shows that the implementation of activity based costing method in determining the diagnostic cost will result more accurate cost so it is feasible to be applied by Laboratorium Klinik Prima for the hematology diagnostic cost is Rp30,700,88; chemical clinic cost is Rp29,081,18; immunology cost is Rp32,044,63 and microbiology cost is Rp29,528,26.Keywords: activity based costing, cost pool rate, cost allocation, cost distortion.